Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1017/s0007114519001235
|View full text |Cite
|
Sign up to set email alerts
|

Association between breakfast skipping and postprandial hyperglycaemia after lunch in healthy young individuals

Abstract: Breakfast skipping has become an increasing trend in the modern lifestyle and may play a role in obesity and type 2 diabetes. In our previous studies in healthy young individuals, a single incident of breakfast skipping increased the overall 24-h blood glucose and elevated the postprandial glycaemic response after lunch; however, it was difficult to determine whether this response was due to breakfast omission or the extra energy (i.e. lunch plus breakfast contents). The present study aimed to assess the postp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 76 publications
(86 reference statements)
3
19
0
Order By: Relevance
“…Better glycemic control was also associated with higher number of eating occasions in two studies performed in adolescents with T1DM [7,13], whereas skipping meals was associated with higher odds of suboptimal HbA1c in a study of 655 children with T1DM [14]. Of particular interest, skipping breakfast has been associated with increased postprandial glycemic response after lunch in a recent, experimental study of healthy young individuals [15]. Regarding physical activity, in a recent study assessing the health and wellbeing of normal Chinese adults living and working after one month of restrictions to contain the COVID-19 outbreak results showed that for those who exercise regularly and over 2.5 h per day, life satisfaction was negatively associated with the level of restrictive measures [5].…”
Section: Discussionmentioning
confidence: 97%
“…Better glycemic control was also associated with higher number of eating occasions in two studies performed in adolescents with T1DM [7,13], whereas skipping meals was associated with higher odds of suboptimal HbA1c in a study of 655 children with T1DM [14]. Of particular interest, skipping breakfast has been associated with increased postprandial glycemic response after lunch in a recent, experimental study of healthy young individuals [15]. Regarding physical activity, in a recent study assessing the health and wellbeing of normal Chinese adults living and working after one month of restrictions to contain the COVID-19 outbreak results showed that for those who exercise regularly and over 2.5 h per day, life satisfaction was negatively associated with the level of restrictive measures [5].…”
Section: Discussionmentioning
confidence: 97%
“…Breakfast skipping has also been confirmed to be associated with a higher incidence of obesity and hyperlipidemia [ 34 ]. In addition, it has been shown that delayed mealtimes or larger calorie intake at dinner leads to obesity with higher postprandial glucose levels [ 35 ]. Hedonic appetite is also higher in the evening, and it is controlled by the circadian clock in the dopaminergic neurons of the ventral tegmental area in mice [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were instructed not to drink alcohol the day before the blood glucose measurement. The sample size of 12 participants for this study was selected on the basis of a previous study [ 21 ] that investigated the effects of skipping breakfast but did not report the effects of eating a late dinner or record blood glucose level fluctuations. The effect size (Cohen’s d) was calculated to be 1.162 (alpha error 0.05, power 0.95).…”
Section: Methodsmentioning
confidence: 99%